ANALISA KERUSAKAN ABUTMEN JEMBATAN KOTO GASIB KABUPATEN SIAK PROVINSI RIAU - Doni Hidayat; Gawit Hidayat (INFO-TEKNIK, 2015)
Koto Gasib bridge is a steel truss bridge class B, located in Koto area Gasib Siak Riau Province, was built as a link road to transport the crop that was built in 2010. By the end of 2013 one of the abutment on the left side of the bridge experienced a rotation of 45 ° causing construction and piles and piles up behind the abutments undergo displacement. Rotation that occurs on the abutments caused due to lateral forces which occur in soil and soil pile axial force received by the foundation abutment causing deflection. Based on the analysis results obtained with the program Geoslope minimum safety factor when the slope backfilled namely SFmin = 0.838 and the results Plaids total displacement of = 1.98 m and a bending moment of = 125.28 kN on the condition of the ground water level of 38.5 meters.Keywords: SFmin, total displacement, bending moment